Mr. Paradise - Leonard, Elmore 1925-2013 (Morrow, 2004)
When party games involving a beautiful escort, her model roommate, lawyer Tony Paradiso, and his aide Montez Taylor go murderously wrong, Detroit detective Frank Delsa finds himself with a double homicide on his hands.
Keywords: Mystery fiction.; Older men -- Crimes against -- Fiction; Police -- Michigan -- Detroit -- Fiction; Witnesses -- Fiction; Young women -- Fiction; Detroit (Mich.) -- Fiction; Mystery fiction